Effect of gingival retraction cord and retraction paste on gingival tissue in fixed prosthodontics impression (Update Dental College Journal, 2014)
Background & Objectives: Of the various gingival retraction systems available in the market, a cordless paste system is fairly new entrant into this field. This system promises to provide an easier method to obtain optimum retraction with excellent hemorrhage control. The present study was designed to clinically evaluate the efficacy of paste retraction system and medicated retraction cords on the basis of relative easy of working, hemorrhage control and amount of vertical gingival retraction. Methods: 40 subjects were selected requiring full veneer restoration where more than one abutment teeth were to be prepared. After the preparation of the abutment teeth flexible scales were used to measure the sulcus depth before retraction and after retraction. Medicated retraction cord technique was used on one abutment tooth and on the other abutment tooth paste retraction system was employed. Subjectively easy of placement and hemorrhage scores was assessed. Results: The mean time taken for paste retraction technique was 45.13 seconds and for medicated retraction cord technique was 105.4 seconds. In all the subjects paste retraction technique was relatively easier as compared with medicated retraction cord technique. Mean hemorrhage scores using paste retraction technique was 0.05 and using medicated retraction cord technique it was 1.70. Mean vertical gingival retraction using paste retraction technique was .36mm and using medicated retraction cord technique was 0.54mm Conclusion: Within the limitations of this study, paste retraction system requires reduced time for application, is easier to place, and provides excellent hemorrhage control in comparison to medicated retraction cord. However, medicated retraction cord provides increased amount of vertical retraction as compared to paste retraction technique. DOI: http://dx.doi.org/10.3329/updcj.v3i2.17995 Update Dent. Coll. j: 2013; 3 (2): 20-27